2013
DOI: 10.4102/sajp.v69i1.366
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life of survivors of trauma six months after discharge

Abstract: 1). eQ-5D vAS was found to be moderately correlated with age (r=-0.4; p=0.05). A negative correlation was found between Sf-36 physical function score and iCu length of stay (loS), hospital respectively). Statistical significance was observed in the correlation between age and Sf-36 general health domain (r=-0.4; p=0.02) as well as age and PCS score (r=-0.5; p=0.01

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…This study contributes to the available limited evidence in South Africa on changes in biopsychosocial outcomes of survivors of critical illness in hospital and over the first 6 months after discharge. The majority of participants were males which is similar to the gender-related demographics described by other South African researchers (Schneiderman et al 2013 ; Van Aswegen et al 2011 ). The participants in this study were older than those described by Schneiderman et al ( 2013 ) and Van Aswegen et al ( 2011 ), and more participants had pre-existing diseases prior to ICU admission.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This study contributes to the available limited evidence in South Africa on changes in biopsychosocial outcomes of survivors of critical illness in hospital and over the first 6 months after discharge. The majority of participants were males which is similar to the gender-related demographics described by other South African researchers (Schneiderman et al 2013 ; Van Aswegen et al 2011 ). The participants in this study were older than those described by Schneiderman et al ( 2013 ) and Van Aswegen et al ( 2011 ), and more participants had pre-existing diseases prior to ICU admission.…”
Section: Discussionsupporting
confidence: 84%
“…The majority of participants were males which is similar to the gender-related demographics described by other South African researchers (Schneiderman et al 2013 ; Van Aswegen et al 2011 ). The participants in this study were older than those described by Schneiderman et al ( 2013 ) and Van Aswegen et al ( 2011 ), and more participants had pre-existing diseases prior to ICU admission. LOS in ICU and hospital was shorter than that described for the polytrauma population by Schneiderman et al ( 2013 ) and the long MV penetrating trunk trauma group in the study by Van Aswegen et al ( 2011 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Individuals who suffer from injury may experience various physical, psychological, social, and cognitive disabilities and impairments (Aitken et al., ). To identify the recovery trajectory of patients after an injury, previous research has followed patients over 3 months (Lee, Chaboyer, & Marianne, ), 6 months (Schneiderman, Van Aswegen, & Becker, ), and 12 to 18 months (Holtslag, van Beeck, Lindeman, & Leenen, ). Previous studies reported that not all injured patients completely recover from their injuries.…”
mentioning
confidence: 99%